2019
DOI: 10.1002/ajpa.23901
|View full text |Cite
|
Sign up to set email alerts
|

The inner ear of the Paranthropus specimen DNH 22 from Drimolen, South Africa

Abstract: Objectives: Morphological variation within the southern African hypodigm of Paranthropus has been the focus of major interest since the earliest discoveries in the "Cradle of Humankind." Given the relevance of the bony labyrinth for investigating fossil primate paleobiodiversity, this article aims to provide additional evidence for assessing the degree of regional variation within Paranthropus through the comparative analysis of the inner ear of DNH 22.Materials and methods: As comparative material, 18 souther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The developmental stability 4 and species-specific features 5 7 of the bony labyrinth, and the relationships between cochlear morphology and auditory perception among mammalian species 8 – 10 , suggest that cochlear shape has the potential to provide evidence about the sensory ecology of extinct hominin taxa. Previous investigations have not detected significant cochlear differences among Plio-Pleistocene australopiths 1 , 2 , 11 . However, the complex shape of the cochlea, comprising a curve of decreasing radius that approximates but does not conform precisely to a logarithmic spiral with different degrees of torsion along its length, does not lend itself to being captured by the linear methods and 3D geometric morphometric (3DGM) approaches that were previously employed.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…The developmental stability 4 and species-specific features 5 7 of the bony labyrinth, and the relationships between cochlear morphology and auditory perception among mammalian species 8 – 10 , suggest that cochlear shape has the potential to provide evidence about the sensory ecology of extinct hominin taxa. Previous investigations have not detected significant cochlear differences among Plio-Pleistocene australopiths 1 , 2 , 11 . However, the complex shape of the cochlea, comprising a curve of decreasing radius that approximates but does not conform precisely to a logarithmic spiral with different degrees of torsion along its length, does not lend itself to being captured by the linear methods and 3D geometric morphometric (3DGM) approaches that were previously employed.…”
Section: Introductionmentioning
confidence: 63%
“…Neither linear measurements nor 3DGM morphometric techniques have been able to discern clear-cut differences between A. africanus , P. robustus and early Homo with respect to their middle ear ossicles 31 , bony labyrinths 1 , 2 , 11 or cochleae 2 , 11 . The present study using diffeomorphometry has shown that the cochlear shapes of both A. africanus and especially P. robustus are distinct from those of modern humans and the African apes.…”
Section: Discussionmentioning
confidence: 99%
“…The morphology of the semicircular canals (SCs), which partly constitute the inner ear's bony labyrinth, has been classically related to locomotion (36)(37)(38)(39)(40)(41)(42). However, several studies have highlighted the possibility of inferring phylogenetic relatedness based on this portion of the inner ear morphology (43)(44)(45)(46)(47) Recently, it has been shown that this anatomical structure also embeds a strong phylogenetic signal among catarrhine primates by means of 3D geometric morphometric (3DGM) analyses (5,(47)(48)(49), thus being potentially useful to test phylogenetic hypotheses for extinct hominoids. Previous studies relied on the SC radius of Rudapithecus hungaricus and Hispanopithecus laietanus to infer slow and deliberate arboreal locomotion for these species (41).…”
Section: Significancementioning
confidence: 99%